Utilization of (Metapenaeus ensis) shrimp heads for shrimp ball - Tumulak, Gina D.
Experiments were conducted to standardize a formulation for shrimp balls using shrimp heads. There were three phases in the study. Phase I dealt with the determination of the most acceptable binder among cassava flour, all-purpose flour and cornstarch. Result of both subjective evaluation and cost accounting revealed that cassava flour gave a shrimp ball of better color and general acceptability. Phase II consisted in the determination of level of usage of cassava flour. In this phase, three level of usage (10%, 25%, 32%, 55% shrimp head's meat) were studied. Result of the subjective tests revealed that the sample with 25% meat gave the best shrimp balls in terms of sensory characteristic and general acceptability. Phase III was the microbiological analysis of the product obtained from Phase II. Standard plate count and detection of Salmonella and Staphylococci were used to monitor the microbiological condition of the product during a storage period of two weeks. Shrimp balls were found to be safe from Staphylococci and Salmonella contamination and the total plate count is within the safe range indicating a product of good quality.